P229 Nocturnal Noninvasive Ventilation Improves Muscle Strength in Stable COPD Patients with Respiratory Failure. (19th November 2012) - Ali, Mir Shad; Talwar, Deepak; Singh, Mandeep
Abstract : Introduction/Objectives: Non-Invasive ventilation (NIV) is established for treatment of patients with COPD and respiratory failure (RF). Respiratory muscle weakness has been reported in these patients. Aim of the study is to see whether nocturnal NIV improves respiratory muscle strength in these patients. Method: 15 stable patients with type II respiratory failure were prospectively given nocturnal NIV at MCRD using Resmed BIPAP at optimal pressure titrated individually for each patient for 8 hours. 7 patients were in control group and were not given nocturnal NIV after obtaining informed consent. Maximal inspiratory, expiratory (PImax & PEmax) and sniff nasal inspiratory pressure (SNIP) were recorded using micro RPM (Care fusion inc.) before and within 5min of removal of nocturnal BiPAP. Paired t-test was used to analyze the recorded data within significant level kept at P<0.05. Result: There was significant increase in PI max & SNIP after nocturnal NIV support in patients with COPD with respiratory failure (38.87±18.2 cmH2O vs 42.07±16.3 cmH2O & 29.2±18.26 cmH2O vs 32.47±17.25 cmH2O; p=0.05 & p=0.048 respectively), but increase in PE max (66.4±18.63 cmH2O vs 68.53±22.0 cmH2O) was stastically insignificant (p=0.37). However significant decrease in PImax & SNIP was observed in the subset of patients who were not given nocturnal NIV (53.14±20.56 cmH2O vs 50.9±21.6 cmH2O, 76.3±20.1 cmH2O vs 71.9±21.8 cmH2O & 38.6±11.7 cmH2O vs 33.7±10.4 cmH2O; p=0.156.0.037 & 0.053 respectively). Conclusion: Nocturnal NIV support in patients with stable COPD with respiratory failure significantly deloads the respiratory muscle, thereby improving inspiratory muscle strength indicating role of NIV in stable COPD patients with respiratory muscle weakness